Assessment of the environmental quality of water resources along the Preto da Eva River in Amazonas, Brazil (Research, Society and Development, 2021)
The impacts on the aquatic environment are constantly being observed in Brazil, and the assessment and monitoring of water resources becomes necessary for a better targeting of planning and environmental management strategies. In this context, the objective of the study is to characterize the quality of the waters of the Preto da Eva river in its physical, chemical and microbiological aspects, and the environmental impacts resulting from the human presence on the river banks. The study was carried out at three points along the Preto da Eva River in the State of Amazonas, during the flood and ebb of the river in 2021. The urban area had greater environmental impact when compared to the rural and peri-urban areas, with a significant difference in quantity of solid waste and noise pollution (p